Evaluation of effects of various drugs on platelet functions using phorbol 12-myristate 13-acetate-induced megakaryocytic human erythroid leukemia cells [Corrigendum] - Tada T; Aki K; Oboshi W; Kawazoe K; Yasui T; Hosoi E (Dove Medical Press, 2017)
Tada T, Aki K, Oboshi W, Kawazoe K, Yasui T, Hosoi E. Drug Des Devel Ther. 2016;10:3099–3107. In page 3103, there is an error in Figure 3B:Read the original article